1993
DOI: 10.1007/bf01213334
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic function in children and adolescents on dialysis and after kidney transplantation: an echocardiographic assessment

Abstract: Thirty-seven children and adolescents on renal replacement therapy (11 on haemodialysis, 14 on continuous ambulatory peritoneal dialysis and 12 after renal transplantation) were studied by echocardiography, echo-Doppler and phonocardiography. Right and left ventricular (R/L V) diastolic functions were measured by transmitral and transtricuspid flow velocities and by LV isovolumic relaxation time (LVIRT). Thirty-seven age- and sex-matched healthy subjects served as controls. R/L V diastolic dysfunction was only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 13 publications
2
29
0
1
Order By: Relevance
“…The most widely used method to determine the diastolic functions of LV is Doppler examination of the mitral inflow velocity. These studies have shown that the LV relaxation (E/A) was impaired in children under dialysis (22,(33)(34)(35). Our Doppler findings were supported by the literature findings.…”
Section: Discussionsupporting
confidence: 91%
“…The most widely used method to determine the diastolic functions of LV is Doppler examination of the mitral inflow velocity. These studies have shown that the LV relaxation (E/A) was impaired in children under dialysis (22,(33)(34)(35). Our Doppler findings were supported by the literature findings.…”
Section: Discussionsupporting
confidence: 91%
“…[4,25] These reports suggested that CAPD has some advantages as a renal replacement therapy for preserving cardiac functions compared to HD in children. In our study, the peak A velocity was increased and E/A ratio was decreased in both CAPD and HD groups when compared to controls whereas there was no change in the peak E velocity among four groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that together with decrease in E/A ratio, the prolongation in IVRT in dialysis patients compared to control group indicates an abnormal myocardial relaxation. [25] . Atalay et al [4] found that peak A velocity was significantly increased and IVRT was significantly prolonged in HD patients when compared with CAPD.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic studies show that young patients with chronic renal insufficiency (CRI) and end-stage renal disease have abnormalities of both left ventricular (LV) structure and function. [1][2][3][4][5] Children with chronic renal disease have a high prevalence of left ventricular hypertrophy (LVH). 1,6 -10 In adults with hypertension and chronic renal failure, LVH is thought to be initially adaptive to improve contractility and lower wall stress (WS) in the face of increased afterload (blood pressure) and preload (volume).…”
mentioning
confidence: 99%